2020
DOI: 10.56369/tsaes.3356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cattle Ovaries and Follicles by Histological Analysis for Potential in Vitro Production of Embryos in Tropical Conditions

Abstract: <p><strong>Background</strong>. Reproduction is important in animal production, and follicle evaluation is a remarkable reproductive aspect by which ovaries can be accurately evaluated since ovarian follicles are the organ's functional units and each contain an oocyte and related somatic cells. <strong>Objective.</strong> The objective of this study was to evaluate the abattoir cattle ovaries and follicles for potential <em>in vitro</em> production of embryos. <stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
0
2
Order By: Relevance
“…Again, the numbers of degenerated primary, secondary and antral follicles were found numerically lower (p>0.05) in CL-ovaries compared to the CL+ ovaries. These findings are not similar to Mahzabin et al (2020) who conducted a histological study on cattle ovaries and found that CL-ovaries contained significantly higher number of total follicles and significantly lower degenerated follicles than ovaries with CL.…”
Section: Histological Studycontrasting
confidence: 99%
See 1 more Smart Citation
“…Again, the numbers of degenerated primary, secondary and antral follicles were found numerically lower (p>0.05) in CL-ovaries compared to the CL+ ovaries. These findings are not similar to Mahzabin et al (2020) who conducted a histological study on cattle ovaries and found that CL-ovaries contained significantly higher number of total follicles and significantly lower degenerated follicles than ovaries with CL.…”
Section: Histological Studycontrasting
confidence: 99%
“…The present study revealed that numerically higher (p>0.05) numbers of small (follicles having 2-6 mm diameter) and large (follicles having >6 mm diameter) follicles were found in the ovaries with CL than CL-ovaries which is not similar to the results of Mahzabin et al (2020).…”
Section: Morphometric Measurements Of Ovary and Folliclescontrasting
confidence: 87%